Clinical and microbiological outcome in septic patients with extremely low 25-hydroxyvitamin D levels at initiation of critical care. (May 2016) - De Pascale, G.; Vallecoccia, M.S.; Schiattarella, A.; Di Gravio, V.; Cutuli, S.L.; Bello, G.; Montini, L.; Pennisi, M.A.; Spanu, T.; Zuppi, C.; Quraishi, S.A.; Antonelli, M.
Abstract: A relationship between vitamin D status and mortality in patients in intensive care units (ICU) has been documented. The present study aims to describe the clinical profile and sepsis-related outcome of critically ill septic patients with extremely low (<7 ng/mL) vitamin D levels at ICU admission. We conducted an observational study in the ICU of a teaching hospital including all patients admitted with severe sepsis/septic shock and undergoing 25-hydroxyvitamin D (25(OH)D) testing within the first 24 hours from admission. We studied 107 patients over 12 months. At ICU admission vitamin D deficiency (≤20 ng/mL) was observed in 93.5% of the patients: 57 (53.3%) showed levels <7 ng/mL. As primary outcome, sepsis-related mortality rate was higher in patients with vitamin D levels <7 ng/mL (50.9% versus 26%). Multivariate regression analysis showed that vitamin D concentration <7 ng/mL on ICU admission (p 0.01) and higher mean SAPS II (p <0.01) score were independent predictors of sepsis-related mortality. Patients with very low vitamin D levels suffered higher rate of microbiologically confirmed infections but a lower percentage of microbiological eradication with respect to patients whose values were >7 ng/mL (80.7% versus 58%, p 0.02; 35.3% versus 68%; p 0.03, respectively). Post hoc analysis showed that, in the extremely low vitamin D group, the 52 patients with pneumonia showed a longer duration of mechanical ventilation (9 days (3.75–12.5 days) versus 4 days (2–9 days), p 0.04) and the 66 with septic shock needed vasopressor support for a longer period of time (7 days (4–10 days) versus 4 days (2–7.25 days), p 0.02). Our results suggest that in critical septic patients extremely low vitamin D levels on admission may be a major determinant of clinical outcome. Benefits of vitamin D replacement therapy in this population should be elucidated.